Acute deep vein thrombosis in a patient with mild COVID-19 infection: An unusual case report - Tolu, Sena; Rezvani, Aylin; Karakaya, Atalay; Eren, Abdulkadir; Basim, Pelin (Annals of Medical Research, 2021)
None